2020
DOI: 10.1021/acsami.0c17423
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Thermal-Annealing-Free Organic Solar Cells Based on an Asymmetric Acceptor with Improved Thermal and Air Stability

Abstract: The stability of organic solar cells (OSCs) is an urgent problem for commercialization. In this work, a novel asymmetric molecule TB-4Cl was designed and synthesized. Quantum chemical computations revealed that TB-4Cl has a larger dipole moment of 1.98 Debye than that of Y6, which can induce a stronger intermolecular interaction. Without thermal annealing, devices based on PM6:TB-4Cl achieved a higher efficiency of 14.67%. Impressively, all of the devices showed a negligible difference in power conversion effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 47 publications
0
40
0
1
Order By: Relevance
“…The newly designed acceptor TB-4F was synthesized according to Scheme . Compound 1 was synthesized according to our previous study . Compound 1 and compound 2 (hyperchemical, 99%) were dissolved in CHCl 3 .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The newly designed acceptor TB-4F was synthesized according to Scheme . Compound 1 was synthesized according to our previous study . Compound 1 and compound 2 (hyperchemical, 99%) were dissolved in CHCl 3 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…For the trade-off of absorption, reducing a thiophene ring of the state-of-the-art molecule Y6 and changing the alky chain could be carried out to obtain the novel asymmetric acceptor TB-4F. A previous study by our group indicated the S-shaped conformation induced by the noncovalent interaction between S and O atoms . Density functional theory (DFT) at the B3LYP/6-31g** level was conducted to study the molecular properties.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Organic solar cells (OSCs), as the third generation photovoltaic technology, have attracted increasing interest over the last few decades due to their advantages of light weight, low cost, easy fabrication and mechanical flexibility. [ 1‐6 ] Especially, the flexible and semi‐transparent (as well as color tunable) active layer turns out to be the most distinguished feature of OSCs, which is superior to conventional silicon‐based solar cells in some special applications. For instance, OSCs are competent to be used in building‐integrated photovoltaic and wearable electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Organic solar cells (OSCs) have achieved rapid development originating from research on the physical characteristics and chemical synthesis of photovoltaic semiconductor materials in this field for several decades. In particular, the successful synthesis of Y6 and its derivative provided OSCs with a maximal power conversion efficiency (PCE) exceeding 19%. However, OSCs need both high performance and excellent long-term stability to realize successful commercialization. When exposed to water, oxygen and irradiation, most organic photovoltaic semiconductor materials inevitably experience chemical degradation. Meanwhile, encapsulation has been used to improve the stabilities of OSCs by effectively preventing the infiltration of oxygen and water . …”
Section: Introductionmentioning
confidence: 99%